Effects of weight loss interventions for adults who are obese on mortality, cardiovascular disease, and cancer: systematic review and meta-analysis. (14th November 2017) - Ma, Chenhan; Avenell, Alison; Bolland, Mark; Hudson, Jemma; Stewart, Fiona; Robertson, Clare; Sharma, Pawana; Fraser, Cynthia; MacLennan, Graeme
Abstract : Objective  To assess whether weight loss interventions for adults with obesity affect all cause, cardiovascular, and cancer mortality, cardiovascular disease, cancer, and body weight. Design  Systematic review and meta-analysis of randomised controlled trials (RCTs) using random effects, estimating risk ratios, and mean differences. Heterogeneity investigated using Cochran's Q and I 2 statistics. Quality of evidence assessed by GRADE criteria. Data sources  Medline, Embase, the Cochrane Central Register of Controlled Trials, and full texts in our trials' registry for data not evident in databases. Authors were contacted for unpublished data. Eligibility criteria for selecting studies  RCTs of dietary interventions targeting weight loss, with or without exercise advice or programmes, for adults with obesity and follow-up ≥1 year. Results  54 RCTs with 30 206 participants were identified. All but one trial evaluated low fat, weight reducing diets. For the primary outcome, high quality evidence showed that weight loss interventions decrease all cause mortality (34 trials, 685 events; risk ratio 0.82, 95% confidence interval 0.71 to 0.95), with six fewer deaths per 1000 participants (95% confidence interval two to 10). For other primary outcomes moderate quality evidence showed an effect on cardiovascular mortality (eight trials, 134 events; risk ratio 0.93, 95% confidence interval 0.67 to 1.31), and very low quality evidence showed an effect on cancer mortality (eight trials, 34 events; risk ratio 0.58, 95% confidence interval 0.30 to 1.11). Twenty four trials (15 176 participants) reported high quality evidence on participants developing new cardiovascular events (1043 events; risk ratio 0.93, 95% confidence interval 0.83 to 1.04). Nineteen trials (6330 participants) provided very low quality evidence on participants developing new cancers (103 events; risk ratio 0.92, 95% confidence interval 0.63 to 1.36). Conclusions  Weight reducing diets, usually low in fat and saturated fat, with or without exercise advice or programmes, may reduce premature all cause mortality in adults with obesity. Systematic review registration  PROSPERO CRD42016033217.